2000
DOI: 10.1179/135100000101535906
|View full text |Cite
|
Sign up to set email alerts
|

The ability of mineral dusts and fibres to initiate lipid peroxidation. Part II: relationship to different particle-induced pathological effects

Abstract: Exposure to pathogenic mineral dusts and fibres is associated with pulmonary changes including fibrosis and cancer. Investigations into aetiological mechanisms of these diseases have identified modifications in specific macromolecules as well as changes in certain early processes, which have preceded fibrosis and cancer. Peroxidation of lipids is one such modification, which is observed following exposure to mineral dusts and fibres. Their ability to initiate lipid peroxidation and the parameters that determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 325 publications
(339 reference statements)
0
2
0
Order By: Relevance
“…[1] Although there is considerable debate and controversy, the literature suggests that there are several factors that influence the potential health effects of these naturally occurring minerals, such as: type of mineral, surface area, length of fibre, atomic structural arrangements, length of time of exposure, oxidative potential (reactive oxygen species -ROS) and surface adherence. [1][2][3][4] It has been suggested that molecular structure determines the potential toxicity of soluble compounds; however, mineral particles' shape, chemical characteristics, size, surface roughness, exposure of crystal planes and surface functional groups all contribute to the ultimate toxicity. [1 , 5] Natural minerals are not thermodynamically stable when exposed to the terrestrial/atmospheric environment and are chemically attacked by naturally occurring acids that alter their chemical structure and thus their chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Although there is considerable debate and controversy, the literature suggests that there are several factors that influence the potential health effects of these naturally occurring minerals, such as: type of mineral, surface area, length of fibre, atomic structural arrangements, length of time of exposure, oxidative potential (reactive oxygen species -ROS) and surface adherence. [1][2][3][4] It has been suggested that molecular structure determines the potential toxicity of soluble compounds; however, mineral particles' shape, chemical characteristics, size, surface roughness, exposure of crystal planes and surface functional groups all contribute to the ultimate toxicity. [1 , 5] Natural minerals are not thermodynamically stable when exposed to the terrestrial/atmospheric environment and are chemically attacked by naturally occurring acids that alter their chemical structure and thus their chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among all profibrogenic molecules, TGFβ1 is most clearly linked to the development of fibrosis during the course of many diseases, including cirrhosis, chronic hepatitis, glomerulonephritis, diabetic nephropathy, atherosclerosis, scleroderma and pulmonary fibrosis [2,4,5,13,28].…”
Section: Introductionmentioning
confidence: 99%